The Oral Health Status of Intellectually and Physically Challenged Children in Central India- A Comparison Study (Update Dental College Journal, 2025)
Introduction: Developmental disabilities includes Down’s syndrome, cerebral palsy,  mental retardation, hearing and visual impairments. They present with compromised oral hygiene. Hence, this study was aimed to study oral  hygiene status of  physically and mentally challenged individuals. Materials and Method: This is a cross-sectional type of survey conducted amongst mentally and physically challenged individuals visiting a camp in Indore. The oral health status was examined using plaque, gingival index and DMFT index. Results: The majority of children brushed once a day with toothbrush and toothpaste (78%). Only 23% of total children had no caries experience. Conclusion: This study exhibited poor oral hygiene amongst children which was statistically significant. (mean plaque score=2.2) between mentally disabled and physically handicapped individuals among oral hygiene and  23% of children had no caries experience. Due to lack of cooperation other risk factors related to oral health status could not be recorded.Update Dent. Coll. j: 2025; 15(1): 6-8